Synthesis, Structure, and Bonding for Bis(permethylpentalene)diiron - Myers, W; O'Hare, D; Binding, S; Green, J (American Chemical Society, 2015)
The synthesis of the first homoleptic double metallocene complex of iron, Fe2Pn*2 (Pn* = permethylpentalene, C8Me6) is described. The structural and electronic properties of Fe2Pn*2 have been characterized by NMR and EPR spectroscopy, single crystal X-ray diffraction, magnetic measurements, cyclic voltammetry, and DFT calculations. Fe2Pn*2 adopts a Ci symmetry in the solid state with a Fe-Fe distance of 2.3175(9) Å, slightly lower than the sum of radii in metallic iron. Magnetic measurements in solution, and of the solid phase between 60 and 300 K, indicate that Fe2Pn*2 is a triplet (S = 1) paramagnet, with effective magnetic moments (μeff) of 3.4 and 3.48 μB, respectively. DFT calculations indicate the origin of this high magnetic moment is likely to be unquenched orbital angular momentum contributions from two SOMOs which have metal d character. Cyclic voltammetry studies demonstrate that Fe2Pn*2 can access four charge states (-1, 0, +1, +2).